2021
DOI: 10.1152/advan.00143.2020
|View full text |Cite
|
Sign up to set email alerts
|

Rat skeletal muscle-nerve preparation to teach skeletal muscle physiology

Abstract: This sourcebook update describes a variation of a previous sourcebook experiment that used isolated extensor digitorum longus muscle from mouse to teach skeletal muscle properties (Head and Arber, Adv Physiol Educ 37: 405-414, 2013; doi:10.1152/advan.00155.2012). Gastrocnemius-sciatic nerve preparation in an anaesthetized rat was developed and muscle contractions were recorded in a computerized data acquisition system using an isometric force transducer. Teachers and students in physiology or biology can use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…That had been suggested that two factors determined it. Firstly, it was because of the superimposed concentric stress [20,32,33,67], which was similar to the effect of excitation frequency occurring at a suitable frequency range. Secondly, it was because muscle fatigue would decrease at a higher speed.…”
Section: Discussionmentioning
confidence: 99%
“…That had been suggested that two factors determined it. Firstly, it was because of the superimposed concentric stress [20,32,33,67], which was similar to the effect of excitation frequency occurring at a suitable frequency range. Secondly, it was because muscle fatigue would decrease at a higher speed.…”
Section: Discussionmentioning
confidence: 99%